A study on status of water contamination of the tube wells in a rural block of North 24 parganas district of West Bengal, India - Lahiri, Saibendu Kumar; Paul, Abhishek; Malick, Suresh Chandra; Bhattacharjee, Somdipta; Mondal, Shatanik; Saha, Partha; Sau, Arkaprabha (International Journal Of Community Medicine And Public Health, 2017)
Background: In India, about 85% of rural drinking water supply depends on groundwater. National Sample Survey, 65th round showed that 55% of rural households were served by a tube well. But ground water pollution has drastically increased in last decade due to increased human activities. In India around 1.5 million children die of diarrhea and 37.7 million people are affected by waterborne diseases annually. The study was conducted to find out the prevalence of contamination of the tube well water and the factors associated with it. Methods: A cross-sectional study was conducted in nine randomly selected villages of the Amdanga Block, North 24-Paraganas district, West Bengal. Water samples of 90 tube wells were tested for the bacteriological contamination using K020 HiH2S Test Strips (Modified) and factors associated with contamination were identified using logit model. Results: The prevalence of tube well water contamination was estimated to be 45.6%. Bacterial contamination of water was found to be significantly (p<0.05) associated with the absence of casing, presence of bad odor in water, presence of habitation within 15 m area and presence of sanitary latrine within 15 m area of tube wells. Conclusions: Ground water pollution is increasing because of human activities, suboptimal maintenance and poor environmental management around the sources. Routine surveillance of water sources, a sustainable system of maintenance and repair, and an effective waste management system in rural areas is required. Emphasis should also be given to household purification of water before consumption.